Do Grittier People Have Greater Subjective Well-Being? A Meta-Analysis. (December 2022) - Hou, Xiang-Ling; Becker, Nicolas; Hu, Tian-Qiang; Koch, Marco; Xi, Ju-Zhe; Mõttus, René
The present study conducted a meta-analysis to examine the relation between grit and subjective well-being (SWB). The association between grit (i.e., overall grit, perseverance of effort, and consistency of interest) and SWB (i.e., positive affect, negative affect, happiness, depression, life satisfaction, job satisfaction, and school satisfaction) were synthesized across 83 studies and 66, 518 participants. The results based on a random-effects model showed a substantial correlation between overall grit and SWB (ρ = .46, 95% confidence interval [CI] = [.43, .48]), followed by perseverance of effort (ρ = .38, 95% CI = [.33, .43]) and consistency of interest (ρ = .23, 95% CI = [.17, .28]). The moderator analysis indicated that the correlations between overall grit/consistency of effort and SWB become weaker as age increased, and these links were stronger in affective well-being than in cognitive well-being. Moreover, grit explained unique variance in SWB even after controlling for conscientiousness. Implications and directions for further research are discussed.